Preparation and in-vitro evaluation of cilostazol self-emulsifying drug delivery system - Ali N. Wannas; Nidhal K. Maraie (College of Pharmacy / Mustansiriyah University, 2020)
This work reported a first liquid self-nanoemulsifying drug delivery system (SEDD) of cilostazol using oleic acid as oil phase, tween 80 as surfactant, and transcutol as co-surfactant. Cilostazol is a poor water-soluble phosphodiesterase III inhibitor, which has antiplatelet   and vasodilator effect used to relief intermittent claudication symptoms. Cilostazol solubility was determined in various oils, surfactants and co-surfactants and phase diagram was constructed at different oil: surfactant: co-surfactant ratios to determine the existence of nano-emulsion region. The in-vitro dissolution profile showed an optimized cilostazol SEDD formula (LT1) containing oleic acid (10%) as oil, tween 80 (45%) as surfactant, and transcutol (45%) as co-surfactant in comparison with the commercial conventionally Tablets. The LT1 formula was thermodynamically sTable, with a zeta potential of -30.48 mV and droplet size 154 nm. The LT1 capsule showed a superior dissolution profile (100%) when compared to the commercial Tablet (64%) of cilostazol. The objective of the present study is to formulate cilostazol as an oral liquid SEDD with better solubility and drug release to overcome a variable bioavailability of the commercial Tablet in which a high-fat meal increases absorption to approximately 90%.